Development of Mesoporous Carbon Composites with Waste Plastics Derived Graphene and MnO2 for Supercapacitor Applications - Murugan, M.; Dineshkumar, G.; Kumar, K. Chaitanya; Tewari, Chetna; Ganesan, M.; Sahoo, Nanda Gopal; Sivanantham, M. (Electrochemical Society, Inc., 2023)
This study demonstrates the influence of incorporating the composites such as waste plastics derived graphene (WPDG) and manganese dioxide (MnO2) in the mesoporous carbon (CR) and their consequent characteristics. The CR having WPDG as composite is named as CRG and MnO2 containing CR composite is termed as CRM. CRG possess the surface area as high as 790 m(2)g(-1) along with pore volume of 0.565 cc g(-1) and radius of 3.82 nm. Cyclic voltammetry (CV) study suggested that CR and CRG showed non-Faradic capacitive behavior with almost rectangular shaped CV profiles at low scan rates and this shows the existence of electric double layer structure. On the other hand, pseudo-capacitance is observed for CRM. Galvanostatic charge/discharge investigation revealed that the specific capacitance can be enhanced by 6 times upon subsequent immobilization of WPDG in CR whereas 4-fold upgrading in the specific capacitance after treating CR with MnO2. Interestingly, CRM showed higher capacitance retention as compared to CRG and is attributed to its smaller value of equivalent series resistance as compared to CRG. Ragone plots shown that the higher energy and power densities are found for the case of CRG.